Improvement of the method for detecting and monitoring the dynamics of the number of chestnut leafminer (Cameraria ohridella Deschka & Dimic) in stands of horse chestnut using color traps - Bashchenko, M.; Chayka, V.; Neverovska, T. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2017)
The possibility of using colored glue traps for detecting and monitoring the dynamics of the number of the chestnut leafminer Cameraria ohridella was studied. The efficiency of the trap is determined depending on the color.